2000
DOI: 10.2337/diabetes.49.9.1525
|View full text |Cite
|
Sign up to set email alerts
|

Obesity induced by a high-fat diet is associated with reduced brain insulin transport in dogs.

Abstract: Insulin transported from plasma into the central nervous system (CNS) is hypothesized to contribute to the negative feedback regulation of body adiposity. Because CNS insulin uptake is likely mediated by insulin receptors, physiological interventions that impair insulin action in the periphery might also reduce the efficiency of CNS insulin uptake and predispose to weight gain. We hypothesized that high-fat feeding, which both reduces insulin sensitivity in peripheral tissues and favors weight gain, reduces th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
197
2
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(212 citation statements)
references
References 40 publications
8
197
2
5
Order By: Relevance
“…This non-linear relationship has been observed in moderate diet-induced obesity rats [37]. High-fat diet-induced obesity is also associated with reduced brain insulin transport in dogs [38], and genetically obese Zucker rats have impaired brain insulin transport [39], which can be ascribed to a decreased number of brain capillary insulin receptors [35]. Here we show that the sites of insulin-signalling impairment seem to be at the IR and post-receptor levels in the hypothalamus of obese Zucker rats.…”
Section: Discussionmentioning
confidence: 64%
“…This non-linear relationship has been observed in moderate diet-induced obesity rats [37]. High-fat diet-induced obesity is also associated with reduced brain insulin transport in dogs [38], and genetically obese Zucker rats have impaired brain insulin transport [39], which can be ascribed to a decreased number of brain capillary insulin receptors [35]. Here we show that the sites of insulin-signalling impairment seem to be at the IR and post-receptor levels in the hypothalamus of obese Zucker rats.…”
Section: Discussionmentioning
confidence: 64%
“…This outcome is strikingly different from the results in normal-weight men where the same treatment reduced hunger and induced a distinct loss of body fat and body weight. 16 It can be concluded that besides impaired blood-to-brain transport of insulin [11][12][13] that in our experiments was overridden by the intranasal administration of the compound, obesity is associated with central nervous resistance against the adiposity signal insulin not only in animals, but also in humans. Concordantly, intranasal insulin failed to acutely suppress food intake in obese men.…”
Section: Discussionmentioning
confidence: 62%
“…10 Animal data indicate that insulin transport to the brain is hampered in the obese state, resulting in a relative CNS deficit of the adiposity signal insulin in genetic and dietinduced models of obesity. 11,12 In humans, obesity appears to be associated with a comparable lack in CNS insulin. 13 Intranasal administration of insulin bypasses the bloodbrain barrier, increasing the concentration of the compound in cerebrospinal fluid without absorption into the blood stream.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, weight gain and insulin resistance from habitual consump-tion of palatable foods decrease insulin and leptin blood-brain barrier (BBB) penetrability (Caro et al, 1996;Kaiyala et al, 2000;Banks, 2003;Banks and Farrell, 2003;Woods et al, 2003) and their CNS effects (Couce et al, 2001;Banks and Farrell, 2003;Lindqvist et al, 2005;Porte et al, 2005), albeit some homeostatic hypothalamic areas lack BBB (Peruzzo et al, 2000;Ganong, 2000). The resultant brain insulin and leptin 'resistance' renders normal satiety signals even more ineffective (Erlanson-Albertsson, 2005;Isganaitis and Lustig, 2005) leading to further impairments in physiologic mechanisms regulating food intake (eg, overeating) and shifting the set point for energy homeostasis towards the development of overweight and obesity (Levine et al, 2003;Erlanson-Albertsson, 2005;Isganaitis and Lustig, 2005).…”
Section: Repetitive Palatable Food Consumption May Dysregulate Homeosmentioning
confidence: 99%